Sports tourism : participants, policy, and providers - Weed, Mike. (Amsterdam : Elsevier, 2004)
Sports Tourism: participants, policy and providers is an essential text for anybody studying this unique topic. Extensively revised with cutting edge new material based on the latest research in the field. . International case studies illustrate how theory is used in practice. Further development of theoretical explanatory frameworks established by this edition .
Part 1. Context -- Part 2. Participants -- Part 3. Policy -- Part 4. Providers -- Part 5. Case studies .
Includes bibliographical references and index.
Keywords: SPORTS AND TOURISM; GEOGRAPHY